MANAJEMEN PELAYANAN UNGGUL DALAM MENINGKATKAN TRUST DAN CITRA PESANTREN - Arifia Retna Yunita; Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to examine the role of excellent service mangement as a strategic approach to improving the reputatuons and public trust of pesantren. This study employs a field research approach at Zaiunul Hasan Genggong Islamic Boarding School (pesantren). The study results reveal that creating a comfortable environment and increasing the satisfaction and trust of student parents require the implementation of service excellence principles, especially in terms of service execution, monitoring and control, friendliness, accuarate information deliverrry, promt responsiveness, responsible conduct nd effective communication. The effective utilization of digital plastforms as a medium for dissemanating infomarmation regarding students activities contributes significantly to stakeholder. These findings underscore the importance of service excellence in fostering trust and enhancing the instutional image of the Isamic boarding school.